Validating Instructional Practice Scale For Instructors In Some Selected Ethiopian Public Universities - Mehari, Anemut (Innovation Journal of Social Sciences and Economic Review, 2024)
The primary aim of this study was to validate the Instructional Practice Scale (IPS) for university instructors in the context of Ethiopian public universities. Recognizing the importance of reliable and contextually appropriate measurement instruments for effective instructional methods, we sought to ensure the IPS was both valid and reliable. The study employed a descriptive survey methodology, gathering data from 1,254 instructors across four public universities. The Smart-PLS were used to analyse the data. The findings provide a robust and reliable instrument for evaluating instructional practices among university instructors. The validated IPS can be effectively used for evaluating and enhancing instructional methods and training programs. Future research should consider adapting and validating the instrument for specific disciplines to further ensure its applicability and accuracy across various educational contexts.
Keywords: Instructional practice; public university instructors; validation; factor analysis; Ethiopian Public Universities